OBJEKTIVITAS BERITA BENCANA GEMPA LOMBOK DI MEDIA ONLINE - Geri Suratno; Indah Suryawati (Fakultas Ilmu Komunikasi - Universitas Budi Luhur, 2019)
An earthquake with 6.4 on the Richter scale that rocked Lombok, West Nusa Tenggara and parts of Bali on July 29, 2018, really attracted the attention of the public. Regarding coverage of natural disasters, the easiest alternative media to get access to information is online media. In fact, the public found that news through online media tended to ignore objectivity, such as elements of completeness, accuracy, fairness, neutrality just to get the publication fastly. The purposes of this study were first, to find out the objectivity of the news presented by Viva.co.id, Kompas.com, and Tribunnewsbali.com during the earthquake and post-earthquake disaster in Lombok from 29 July to 29 August 2018, and the second, to describe the roles of Viva.co.id, Kompas.com, and Tribunnewsbali.com in reporting the earthquake in Lombok during this period. The focus of online media content analysis is on the elements of objectivity, truth, factual, accuracy, complete and neutrality. The research method used is the content analysis method using a quantitative approach. The object of this research was the Lombok earthquake news reported by Viva.co.id, Kompas.com and Tribunnewsbali.com period July 29 to August 29, 2018. The results showed that Viva.co.id, Kompas.com and Tribunnewsbali.com prioritized sub-dimensions truth in upholding objectivity. Where the sub dimensions of truth are divided into three elements, those are factual, accuracy and complete. But Viva.co.id and Tribunnewsbali.com ignored the sub-dimensions of neutrality. While kompas.com didn’t ignore the sub-dimensions of neutrality. Even though the sub-dimensions of neutrality are part of the dimension of objectivity.